Про існування розв’язку та усереднення багатоточкових крайових задач для багаточастотних систем із лiнiйно перетвореним аргументом - Бігун, Я.Й. (Нелінійні коливання, 2008)
Для m-частотной системы дифференциальных уравнений с линейно преобразованным аргументом доказано существование решения, которое удовлетворяет начальным или многоточечным краевым условиям. Получена оценка погрешности метода усреднения по быстрым переменным, явно зависимая от малого параметра. For an m-frequency system of differential equations with linearly transformed argument, we prove existence of a solution that satisfies the initial or multipoint boundary-value conditions. We find an estimate, which explicitly depends on the small parameter, for the error of the method of averaging in the fast variables.